Effects of Active Assisted and Isometric Exercises Combined with Ultrasound in Knee Osteoarthritis - Ida Ayu Astiti Suadnyana; I Putu Prisa Jaya; IA Pascha Paramurthi; Nyoman Dwi Sutrisnawati (Jurnal Keterapian Fisik, 2025)
Background: Knee Osteoarthritis is a chronic degenerative joint disease of the knee cartilage which is characterized by pain and joint stiffness which has an impact on the functional activities of the elderly. Physiotherapy has an important role in reducing pain by using electrotherapy modalities (ultrasound) and also exercise therapy (active assisted exercise and isometric exercise) The aim of this study is to determine the difference in effectiveness between adding active assisted exercise and isometric exercise to ultrasound intervention in reducing pain among elderly patients with knee osteoarthritis. Methods: This research was conducted at the Physiotherapy Clinic of Merdeka Medical Center from June to July 2024. The study used an experimental pre-test–post-test control group design with purposive sampling. Twenty-six elderly participants were selected and allocated into two groups of thirteen participants each. Knee pain was measured using the Visual Analogue Scale (VAS), administered before and after the intervention in both groups. Data were analyzed using SPSS. Based on the results of the paired samples t-test in groups 1 and 2. Results: The p value was 0.001, indicating a significant difference between group 1 and group 2 in reducing pain. Isometric exercise combined with ultrasound reduced knee pain by 51.3% more than active assisted exercise combined with ultrasound in elderly patients with knee osteoarthritis.  Conclusion: Isometric exercise with ultrasound reduces knee pain in the elderly compared to active assisted exercise. Therefore, isometric exercise with ultrasound should be recommended as a preferred physiotherapy intervention to reduce pain in this population.